MECHANICAL PROPERTIES OF THE SURFACE LAYER OF CUBIC BORON NITRIDE-BASED COMPOSITES - Клименко, Сергій; Закієв, Вадим; Манохін, Андрій; Мельнійчук, Юрій; Копєйкіна, Марина; Клименко, Сергій; Чумак, Анатолій; Рябченко, Сергій (SWorldJournal, 2025)
The article investigates the mechanical properties of the surface layer of superhard composites based on cubic boron nitride (cBN), which are widely used in cutting tools operating under extreme thermomechanical conditions. The purpose of the work is to j